New method for GHG measurements with closed chambers at night time - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Eddy Covariance data sets over 4 cropping seasons have been analyzed and linear relationship between nocturnal fluxes and the full 24-hour fluxes could be shown. The proof-of-concept has been provided with actual chamber measurements at nighttime.